Optimization of Three-Phase Load Balancing to Improve the Efficiency and Reliability of Power Transformers at the Tanjung Morawa Substation - Arnold Fernando Sinurat; Moranain Mungkin (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2026)
Three-phase load imbalance in power transformers is one of the main problems that can reduce efficiency, increase power losses, accelerate the increase in winding temperature, and reduce the life of transformer insulation. This condition often occurs in distribution systems due to uneven load growth between phases. This study aims to optimize three-phase load balancing to improve the efficiency and reliability of power transformers at the Tanjung Morawa Substation. The research method uses a quantitative approach based on transformer operational data, including measuring the current of each phase, calculating the percentage of load imbalance, analyzing copper losses, and evaluating efficiency and reliability indices. The optimization model is carried out by simulating load redistribution between phases using a mathematical approach to minimize current deviations from the average current. Evaluation parameters include reducing power losses, increasing transformer efficiency, and improving the value of the imbalance factor according to IEC and IEEE standards. The results show that before optimization, the level of load imbalance was in the moderate to high category, which resulted in increased power losses and increased operating temperatures. After the load balancing optimization process, there was a significant decrease in the percentage of imbalance, a decrease in power losses, and an increase in transformer efficiency. Furthermore, the estimated insulation life shows an improvement due to reduced thermal stress. This study demonstrates that a systematic, data-driven three-phase load balancing optimization strategy can sustainably improve the performance, efficiency, and reliability of power transformers. The proposed model can be implemented as part of an asset management and preventive maintenance strategy in electric power systems.